Pengembangan Kompetensi PAI Berbasis Nilai Multikulturan dan Kearifan Lokal di Perguruan Tinggi Indonesia - Izzatul Mardhiah; Andy Hadiyanto; Amaliyah Amaliyah; Ahmad Hakam (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2021)
This study aims to identify the competencies developed from multicultural values ​​and local wisdom in Indonesian society in Islamic Religion Education in Higher Education. This research method is qualitative, the technique of collecting data uses interviews, questioner, observation, study documentation, and focus group discussions. The subjects were lecturers and students participating in Islamic Religious Education learning. The study results found two main components, the competence of Islamic Religious Education Learning in Higher Education, which is based on multicultural values and local wisdom, and the development of indicators and instruments for assessing attitudes. The contribution of this research is the revitalization of the curriculum on the learning outcomes of Islamic education in the affective domain and cultivate multicultural values and local wisdom through Islamic Religious Education Learning in Higher Education.